Post-esophagectomy chylothorax refractory to mass ligation of thoracic duct above diaphragm: a case report - Shengxi Wang; Wenpeng Jiang (Journal of Cardiothoracic Surgery, 2022)
Abstract Background Post-esophagectomy chylothorax is a relatively rare but potentially lethal complication. The treatment strategy of post-esophagectomy chylothorax remains a subject of debate which mainly focuses on the indication and timing of surgical intervention. For cases in which the leakage site is not localized, a mass ligation of the thoracic duct above diaphragm is advocated as the surgical procedure is believed to ensure sealing all the accessory ducts that could be the source of the chylothorax. But in this paper, we report a case of post-esophagectomy chylothorax which was refractory to mass ligation of thoracic duct above diaphragm. Case presentation A 59-year old man suffered from high output chylothorax (> 1000 ml/24 h for more than 30 days) after esophagectomy through left thoracotomy. Considering the failure of lymphangiography, we performed mass ligation of thoracic duct above diaphragm. However, we failed to close the chylous leakage. Finally, we found that a rare variated tributary of thoracic duct was the resource of the chylous output. Both the variation of lymphatic system and the coincidence of injured site lead to the invalidness of reoperation. After definitely ligating the variated tributary, chylothorax was cured. Conclusion This case supplies a direct evidence that mass ligation of thoracic duct is of no avail in some refractory chylothorax, which indicates the importance of chylous leakage localization.